2008
DOI: 10.1037/0097-7403.34.2.223
|View full text |Cite
|
Sign up to set email alerts
|

Contextual control of inhibition with reinforcement: Adaptation and timing mechanisms.

Abstract: Four experiments with rats studied the effects of switching the context after Pavlovian conditioning. In three conditioned suppression experiments, a large number of conditioning trials created "inhibition with reinforcement" (IWR), in which fear of the conditional stimulus (CS) reached a maximum and then declined despite continued CS-unconditional stimulus pairings. When IWR occurred, a context switch augmented fear of the CS; IWR and augmentation were highly correlated. Neither IWR nor augmentation resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
50
4
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 54 publications
3
50
4
1
Order By: Relevance
“…Superficially, the observations of Experiment 1 are inconsistent with the results of Bouton et al (2008) and Pickens et al (2009), because we observed a reliable PPD effect outside of the training context, whereas the results of Bouton et al and Pickens et al suggested that recovery from the PPD is observed when the test is conducted outside of the physical or temporal context of training. As mentioned in the introduction, Urcelay and Miller's (2010) observations become relevant for the present discussion because a comparison of the parameters used in Experiment 1 with those used by Bouton et al and Pickens et al shows that they were indeed widely different.…”
Section: Methodscontrasting
confidence: 57%
See 4 more Smart Citations
“…Superficially, the observations of Experiment 1 are inconsistent with the results of Bouton et al (2008) and Pickens et al (2009), because we observed a reliable PPD effect outside of the training context, whereas the results of Bouton et al and Pickens et al suggested that recovery from the PPD is observed when the test is conducted outside of the physical or temporal context of training. As mentioned in the introduction, Urcelay and Miller's (2010) observations become relevant for the present discussion because a comparison of the parameters used in Experiment 1 with those used by Bouton et al and Pickens et al shows that they were indeed widely different.…”
Section: Methodscontrasting
confidence: 57%
“…In particular, we assessed whether this effect could be observed when testing was conducted outside the training context, a finding that would contrast with the results by Bouton et al (2008) showing recovery from the PPD when the test is conducted outside of the context of PPD training. Four groups of rats received 5, 10, 20, or 50 pairings of a clicker with a mild footshock.…”
Section: Methodsmentioning
confidence: 62%
See 3 more Smart Citations